PENGARUH UPAH DAN KEMAHALAN KONSTRUKSI TERHADAP PENGELUARAN PER KAPITA DI PROVINSI NUSA TENGGARA TIMUR TAHUN 2019-2024 - Ahsan Anwar Basari (Badan Pusat Statistik Provinsi NTT, 2026)
Introduction/Main Objectives: Household welfare is commonly measured by per capita expenditure, which reflects consumption capacity. In Nusa Tenggara Timur Province (NTT), welfare conditions are characterized by low per capita expenditure and low wage levels, along with relatively low regional cost levels as reflected by the Construction Cost Index (IKK), which is used as a proxy indicator to capture regional price disparities. Background Problems: Theoretically, such conditions should provide room for higher purchasing power; however, empirical evidence is still required to confirm this relationship. Novelty: This study provides recent study on the effects of wages and the Construction Cost Index (IKK) on per capita expenditure in NTT. Research Methods: This study aims to analyze the effect of wages and the IKK on per capita expenditure across 22 regencies/municipality in NTT during the period 2019-2024. The study uses panel data obtained from official publications of the Badan Pusat Statistik (BPS). The analysis is conducted using a Fixed Effect Model (FEM) estimated with Feasible Generalized Least Squares (FGLS). Finding/Results: show that wages have a positive but not significant effect on per capita expenditure at the 5 percent level of significance but are statistically significant at 10 percent, while the IKK has a negative and significant influence at the 5 percent significance level. These findings indicate that income improvements increase consumption, whereas regional cost conditions remain a constraint on household welfare.